Psychological wellbeing and mental health outcomes in Australian Nurses and Midwives - Louise Gibson; Kimberley Norris (Archives of Nursing Practice and Care - Peertechz Publications, 2022)
Aim: To examine the intrapersonal and organizational factors that contribute to pathogenic and salutogenic psychological outcomes in Australian nurses and midwives.  Design: The conceptual framework Factors associated with Salutogenic and Pathogenic Outcomes in Australian Midwives and Nurses was used as a guide for this exploratory, cross-sectional study. Method: Participants were recruited from public, private, and community settings throughout Australia. Six hundred and fifteen participants completed an online survey assessing job satisfaction, professional quality of life, ways of coping, resilience, psychological distress, and the impact of the worldwide coronavirus pandemic on psychological health and well-being. Results: Analyses showed that workplace environmental factors were strong predictors of Secondary Traumatic Stress, and Burnout. Results also showed that workplace factors and adaptive coping were predictive of the salutogenic outcomes of compassion satisfaction and resilience. Conclusion: Adopting a salutogenic approach, focused on maximizing individual and organizational contributors to psychological health and wellbeing, provides a new way for organizations to develop strategies to decrease adverse psychological outcomes, promote well-being and better equip nurses and midwives to cope with the challenges of the healthcare environment. Impact: The findings will be of interest to Chief Nurses, Midwifery Officers, healthcare organizations, and universities to target workplace, individual and interpersonal factors that promote health and wellbeing amongst nurses and midwives.